2009
DOI: 10.1111/j.1523-5378.2009.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter hepaticus in Human Bile Samples of Patients with Biliary Disease

Abstract: Background:Since the discovery of Helicobacter pylori, various enterohepatic Helicobacter spices have been detected in the guts of humans and animals. Some enterohepatic Helicobacters have been associated with inflammatory bowel disease or liver disease in mice. However the association of these bacteria with human diseases remains unknown.Materials and Methods:We collected 126 bile samples from patients with cholelithiasis, cholecystitis, gallbladder polyp, and other nonbiliary diseases. Samples were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 20 publications
(20 reference statements)
1
43
0
Order By: Relevance
“…Controls have typically comprised subjects with biliary tract diseases such as gallstones or cholecystitis. Since these diseases have also been linked to enterohepatic Helicobacter, the use of these patients as controls may be inadequate (98). With these caveats, there has been wide variability in the study findings, from no association to a 6-fold increase in the odds of gallbladder cancer with Helicobacter infection.…”
Section: Alterations Of Normal Host Responses Chronic Inflammationmentioning
confidence: 66%
See 1 more Smart Citation
“…Controls have typically comprised subjects with biliary tract diseases such as gallstones or cholecystitis. Since these diseases have also been linked to enterohepatic Helicobacter, the use of these patients as controls may be inadequate (98). With these caveats, there has been wide variability in the study findings, from no association to a 6-fold increase in the odds of gallbladder cancer with Helicobacter infection.…”
Section: Alterations Of Normal Host Responses Chronic Inflammationmentioning
confidence: 66%
“…Eight studies of humans have evaluated the presence of Helicobacter species in biliary tracts of cancer patients versus controls. These studies have had significant differences in their methods of bacterial detection, including culture, DNA amplification, and immunohistochemistry (58,98). Controls have typically comprised subjects with biliary tract diseases such as gallstones or cholecystitis.…”
Section: Alterations Of Normal Host Responses Chronic Inflammationmentioning
confidence: 99%
“…and commensal organisms (commensal E. coli and Lactobacillus salivarius) have been associated with human gallbladder infection (cholecystitis) (1,19,40,51). Bacterial colonization of the gallbladder has also been implicated in gallstone formation, although a direct causal link has not been definitively established (30).…”
Section: Discussionmentioning
confidence: 99%
“…(EHS) may be involved in hepatobiliary diseases of humans. 15,[36][37][38][39] Although H. hepaticus was not detected in the stools of HCV or hepatitis B virus patients with HCC, a previous study from our laboratory indicated that H. hepaticus promoted liver cancer in B6C3F1-Tg(Alb1-HCVN)35Sml mice and also promoted aflatoxin-induced liver cancer in C3H/HeNCr mice with persistent intestinal colonization of H. hepaticus, despite the lack of the organism in the liver. 22,40 The occurrence of HCCs in H. pylori-infected and uninfected HT and WT mice in our study is consistent with the natural susceptibility of aged B6C3F1 male mice to liver tumors.…”
Section: Hcv Transgene Increases Serum Tnf-α During H Pylori Infectimentioning
confidence: 99%